The Effects on Cardiovascular Autonomic Control of Repetitive Arousal from Sleep - Chaicharn, J. (Associated Professional Sleep Societies, LLC, 2008)
STUDY OBJECTIVES: To quantitatively assess autonomic cardiovascular control in normal young adults following exposure to repetitive acoustically-induced arousals from sleep. DESIGN: Respiration, R-R interval (RRI) and noninvasive measurements of continuous arterial blood pressure were monitored in subjects during the transition from relaxed wakefulness to stable Stage 2 sleep. These measurements were made under undisturbed conditions or conditions in which transient arousals were induced repetitively by acoustic stimulation. A mathematical model was used to partition the fluctuations in RRI into a component (“RSA”) correlated with respiration and a component (“ABR”) representing baroreflex control of heart rate. The magnitudes and forms of each component before and after exposure to repetitive arousals were compared SETTING: Sleep disorders laboratory in a university setting. PATIENTS OR PARTICIPANTS: Ten healthy young adults (5 male, 5 female) with an average age of 20.4 ± 2.0 y and mean body-mass index of 23.8 ± 2.9 kg/m(2). INTERVENTIONS: Each subject participated in multiple sleep studies consisting of 4 conditions with 2 nights in each condition. The first condition consisted of undisturbed sleep (control), while in the other 3 conditions, the subjects were aroused from sleep by repetitive auditory stimuli applied continuously over a duration of 50 minutes, with periodicities of 30 seconds, 1 minute, and 2 minutes of sleep. MEASUREMENTS AND RESULTS: Exposure to repetitive arousal (RA) did not alter mean heart rate or blood pressure. However, ABR and RSA gains estimated using the model, increased from the onset of Stage 1 sleep to the start of stable Stage 2 sleep under the control condition, but remained unchanged in all RA conditions. There were also significant increases in low-frequency oscillations of systolic blood pressure in the RA conditions versus no change in the control condition. CONCLUSIONS: Exposure to RA over durations approximating an hour produces cumulative effects on autonomic control that are subtle and can only be detected when advanced signal processing methods are employed. More specifically, the increases in ABR and RSA gains that accompany increasing sleep depth in normal sleep are prevented from occurring. CITATION: Chaicharn J; Carrington M; Trinder J; Khoo MCK. The Effects on Cardiovascular Autonomic Control of Repetitive Arousal from Sleep. SLEEP 2008;31(1):93-103.